1999
DOI: 10.1136/gut.44.5.709
|View full text |Cite
|
Sign up to set email alerts
|

Vicia faba agglutinin, the lectin present in broad beans, stimulates differentiation of undifferentiated colon cancer cells

Abstract: (Gut 1999;44:709-714)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(33 citation statements)
references
References 31 publications
1
31
0
1
Order By: Relevance
“…A large number of studies with PNA indicate that this lectin acts in a cell type specific manner, often promoting proliferation and sometimes producing a toxic effect (Lee 1988;Caldero et al, 1989;McGarrity et al, 1991;Boland et al, 1992;Ryder et al, 1992;Chen et al, 1994;Kiss et al, 1997;Lorea et al, 1997;Jordinson et al, 1998;Yu et al, 2001;Singh et al, 2001;2006;Ohba et al, 2003;Cai et al, 2005). Valentiner et al (2003) in a model study showed that different lectins exerted different effects at specific concentrations on different breast cancer cell lines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A large number of studies with PNA indicate that this lectin acts in a cell type specific manner, often promoting proliferation and sometimes producing a toxic effect (Lee 1988;Caldero et al, 1989;McGarrity et al, 1991;Boland et al, 1992;Ryder et al, 1992;Chen et al, 1994;Kiss et al, 1997;Lorea et al, 1997;Jordinson et al, 1998;Yu et al, 2001;Singh et al, 2001;2006;Ohba et al, 2003;Cai et al, 2005). Valentiner et al (2003) in a model study showed that different lectins exerted different effects at specific concentrations on different breast cancer cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…In the study reported here, we examine two lectins that are reported to be largely non-toxic to cells -Dolichos biflorus agglutinin (DBA) and Arachis hypogaea /peanut agglutinin (PNA) (Ryder et al, 1992;Chen et al, 1994;Camby et al, 1997;Kiss et al, 1997;Jordinson et al, 1998;Ohba et al, 2003;Valentiner et al, 2003;Singh et al, 2006) -using a human colon cancer (CCL-220) and a human non-cancer colon CRL-1459) cell line, as in our previous studies (Khurrum et al, 2002;Heinrich et al, 2005;Welty et al, 2006). We did not want to use toxic lectins that kill cells quickly.…”
Section: Introductionmentioning
confidence: 99%
“…Overexpression of Ep-CAM is linked to differentiation and cell proliferation (Jordinson et al, 1999), although the molecular mechanism is still poorly understood. In vitro, its overexpression has been shown to be directly linked to stimulation of the cell cycle and proliferation by upregulating c-myc and cyclin A/E .…”
mentioning
confidence: 99%
“…~ ~sm for _ti 'w~__ altermior~ is not yet unde~oocl, it was suggested that might he responsible for the ch~n~ obr~nced on the e~/dln:)cyte surface. In case of GanGer breast cases there may be increase in galactose epitopes as Studies ~ated with cell membrane changes and lec0n agglutination stmu~d that binding sites differ in different stages (10). In our study although cases at different stages were present, stage wise analysis was not carried out.…”
Section: Results and Di~u8810nmentioning
confidence: 68%